2016
DOI: 10.1021/acs.jpcb.6b04033
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ions on Individual Water Entropy

Abstract: Solutes determine the properties of a solution. In this study, we probe ionic solutions through the entropy of individual water molecules in the solvation shells around different cations and anions. Using a method recently developed by our group, we show the solvation shell entropy stemming from the individual contributions correlates extremely well with experimental values for both polarizable and nonpolarizable force fields. The behavior of water entropy as a function of distance reveals significant (∼20%) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 67 publications
3
19
0
1
Order By: Relevance
“…In particular, at comparable sizes, anions induce a more pronounced perturbation of their hydration shells compared to cations, because they are hydrogen-bond acceptors. 17,50,113,268,282,294,[296][297][298][299][300][301][302] The same applies to small or/and multivalent ions, because they generate a stronger electric field at their surface. This more important perturbation may require the inclusion of the second hydration shell into the QM region.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, at comparable sizes, anions induce a more pronounced perturbation of their hydration shells compared to cations, because they are hydrogen-bond acceptors. 17,50,113,268,282,294,[296][297][298][299][300][301][302] The same applies to small or/and multivalent ions, because they generate a stronger electric field at their surface. This more important perturbation may require the inclusion of the second hydration shell into the QM region.…”
Section: Discussionmentioning
confidence: 97%
“…This result also agrees with a theoretical analysis on individual water entropy around ions, which showed that the rotational entropy reduction of the first solvation shell water molecules near Cl À is almost half compared to that around Mg 2 + . [93] The retardation of the water dipole reorientation near ions, including Mg 2 + , [94] has also been discussed in the "jump model" by Stirnemann et al to explain the long-and short-range effects of Mg 2 + on the orientation time correlation function. Our finding that subpopulations such as W 211 and W 212 in MgCl 2 (aq) have a slow reorientation dynamics compared to bulk behaviour supports previous investigations of electrolyte solutions reporting on the long-range effects of ions, beyond their first hydration shell.…”
Section: Reorientation Dynamics In Different Subpopulationsmentioning
confidence: 99%
“…The latter allows computing a local covariance matrix for each solvent molecule to estimate its configurational entropy. This approach can be extended to allow for solvation entropy estimations and to include spatial resolution of local contributions via the reference positions of the solvent molecules …”
Section: Solvation Entropy and Spatial Resolutionmentioning
confidence: 99%
“…However, PRPCA was shown to reproduce experimental data for the solvation entropy of various ions with good accuracy, demonstrating that quantitative descriptions are feasible in such systems. 45 To evaluate the performance of each approach in terms of accuracy as well as computational efficiency, it would be highly desirable to compare them side by side using identical simulation trajectories with converged thermodynamic integration data as a reference. Such an approach is more insightful than comparisons to experimental data, because intrinsic errors of the underlying force field model cancel out in the comparison.…”
Section: Solvation Free Energiesmentioning
confidence: 99%